Role of Contrast-Enhanced CT and Serum Alpha-Fetoprotein in Early Detection of Hepatocellular Carcinoma - Naeem Ahmad Khan, Beenish Javaid, Fatima Iqbal, Nazish Khalid, Attka Maryam, Muhammad Ahmad Raza Butt (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Early detection of hepatocellular carcinoma (HCC) remains a global challenge due to itsasymptomatic course and high mortality. Serum alpha-fetoprotein (AFP) is widely used insurveillance but suffers from limited sensitivity and specificity, especially for small lesions. Contrast-enhanced computed tomography